Audit IT Aplikasi Online Single Submission (OSS) versi 1.1 dengan COBIT 5.0 - Pratiwiyani Pratiwiyani; Sri Huning Anwariningsih; Firdhaus Hari Saputro Al Haris (Program Studi Teknik Industri Universitas Setia Budi, 2020)
Investment and One Stop Integrated Service Office (DPMPTSP) is a government agency that serves licensing and investment that uses the information system from BKPM RI, OSS 1.1. DPMPTSP of XYZ City found several obstacles in the use of OSS 1.1, including OSS 1.1 unable to display reports based on the type of permit, there were some licenses that were not integrated yet, there was no link with the licensing agency, so an OSS 1.1 system audit was needed. with a case study in DPMPTSP XYZ City. This audit aims to determine the OSS system capability level 1.1. which refers to the implementation process in DPMPTSP. The method used is descriptive qualitative with primary data type in the form of data from interviews with DPMPTSP. Data collection was carried out by interview and question methods from the COBIT 5 domain. Based on the results of an audit of research conducted using the CobIT 5.0 framework, resulting in a level of capability and recommendations. The current OSS system capability level 1.1, Evaluate, Direct and Monitor (EDM) domains are at capability level 2.6 (Managed), Align, Plan and Organize (APO) domains are at capability level 2.4 (Managed), Build domain, Acquire and Implement (BAI) are at capability level 2.3 (Managed), Deliver domains, Service and Support (DSS) are at capability level 2.3 (Managed), Monitor, Evaluate and Assess (MEA) domains are at level capability 2.6 (Managed). In this condition OSS 1.1 system governance has been implemented well in XYS City DPMPTSP with several recommendations to DPMPTSP so that it can be submitted to BKPM RI to improve OSS 1.1 system governance so that it runs more optimally.